Exploring Transformational Generative Grammar in Arabic Textbooks for Junior High School: A Qualitative Library Research - Muyasiroh, Wildatul; Mubin, Khoirul; Muyasaroh, Wildatul; Ashfia, Ahmad; Zulfa, Aghitsna Waliyaz (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study addresses students’ difficulties in learning Arabic due to the limited relevance of existing textbooks. Using Chomsky’s Transformative-Generative Grammar Theory (TGT) as an analytical framework, the research explores the application of singular transformation rules in the ninth-grade Arabic textbook published by the Ministry of Religious Affairs. Chomsky’s theory, which emphasizes grammatical structure and transformation processes, is applied to improve students’ grammatical and communicative competence. Employing a qualitative descriptive design with a library-based approach, the study identifies six transformation rules: elimination, expansion, addition, change of order, replacement, and abbreviation. The findings indicate that integrating TGT into Arabic instruction through methods such as the Direct Method can enhance students’ grammatical understanding and vocabulary mastery. The study suggests that future research examine other linguistic aspects of similar textbooks to further strengthen the pedagogical application of linguistic theory in Arabic learning.